A context-based approach for modelling and querying versions of BPMN processes. (16th February 2021) - Chaâbane, Mohamed Amine; Said, Imen Ben; Ellouze, Fatma; Bouaziz, Rafik; Andonoff, Eric
Versioning is an interesting solution to deal with business process flexibility. It consists of the definition of several process versions for taking into account the significant changes occurring to the processes. It allows the running of several instances of the same process according to different models. However, in a multi-version environment, where numerous versions co-exist, it is important to specify the context in which these versions can be used. The context is used in particular to find out, for a given situation, the appropriate process version to be executed at run-time. We aim in this paper at offering a solution to model the context of versions of intra- and inter-organisational processes and query these versions using their context. More precisely the recommended solution extends BPMN2.0, the de-facto standard for process modelling, to consider versions and contexts, and introduces a context based language for versions querying.